An Injectable Antibiotic Hydrogel that Scavenges Proinflammatory Factors for the Treatment of Severe Abdominal Trauma. (7th April 2022) - Yang, Chao; Dawulieti, Jianati; Zhang, Kunbao; Cheng, Chuanxu; Zhao, Yawei; Hu, Hanze; Li, Mingqiang; Zhang, Ming; Chen, Li; Leong, Kam W.; Shao, Dan
Abstract: Bacterial infection and excessive inflammation following abdominal injury can cause life‐threatening complications that lead to multiple organ failure and death. Removing bacteria and proinflammatory factors—which are predominantly negatively charged—from the wound site with a cationic, antibiotic‐containing hydrogel wound dressing is therefore a promising treatment approach for severe abdominal trauma. Here an injectable, self‐healing hydrogel composed of the gel‐forming glycosaminoglycan oxidized chondroitin sulfate (OCS), cationic polyethylenimine (PEI), and the antibiotic tobramycin (Tob) via a Schiff's base reaction is developed. Compared with hydrogels lacking either PEI or Tob, only the Tob/PEI/OCS hydrogels exhibit a large binding capacity for negatively‐charged proinflammatory factors including cell‐free DNA, lipopolysaccharides, TNF‐α, and high mobility group box 1 protein, and a large reduction in bacterial populations in vitro. In a murine model of severe abdominal trauma, the Tob/PEI/OCS hydrogel exhibits good biodegradability and biosafety, reduced local and systemic inflammation and infection, and prevents multiple organ failure, resulting in 100% survival. This hydrogel dressing is thus a promising biomaterial for preventing complications and improving outcomes following severe abdominal trauma. Abstract : An injectable, self‐healing, and cationic hydrogel exhibiting a large binding capacity for negatively charged proinflammatory factors including cell‐free DNA, lipopolysaccharides, TNF‐α, and high mobility group box 1 protein is developed. Such a bioactive hydrogel reduces local and systemic inflammation and infection, and prevents multiple organ failure, resulting in 100% survival in a murine model of severe abdominal trauma model with good biodegradability and biosafety.